Analisis Efektivitas Implementasi Kebijakan Tindak Pidana Perdagangan Orang di Kabupaten Timor Tengah Selatan - Januard Anggara Ottu; Petrus Kase; Rouwland Alberto Benyamin; Mariayani O. Rene (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
Human trafficking remains one of the most serious transnational crimes and continues to pose significant challenges to public policy implementation, particularly in regions with high labor migration rates. This study aims to analyze the implementation of the policy on the prevention and handling of human trafficking in Timor Tengah Selatan Regency, East Nusa Tenggara Province, based on George C. Edward III's policy implementation model. A qualitative descriptive approach was employed using in-depth interviews, observation, and document analysis. Data were analyzed through the interactive model of Miles, Huberman, and Saldaña, consisting of data condensation, data display, and conclusion drawing. The findings indicate that policy implementation has involved collaboration among local government agencies, law enforcement institutions, village governments, religious organizations, and civil society organizations. Communication, implementers' commitment, and bureaucratic coordination have generally functioned well; however, limited resources, uneven public outreach, and suboptimal operational coordination remain significant barriers. The implementation has produced outputs in the form of strengthened inter-agency coordination, expanded public awareness campaigns, improved monitoring of prospective migrant workers, and enhanced victim assistance services. Nevertheless, the policy outcomes have not been fully optimal due to uneven public awareness, limited victim rehabilitation facilities, and insufficient institutional capacity. Strengthening local regulations, increasing resource allocation, and promoting community-based prevention strategies are essential to improve the effectiveness and sustainability of anti-human trafficking policies.